Profile of students conservation attitudes in forest management and plant diversity management based on local wisdom - Sari, Defita Permata; Susanti, Try (Universitas Negeri Jakarta, 2024)
The diversity of plant species found in the Temedak customary forest is relatively high but residents should not use it freely. Residents are prohibited from cutting or taking wood from the forest, they can only take fruit, rattan and bamboo for their own consumption and must have the permission of local traditional leaders. The higher the diversity of plants found in the Temedak customary forest, the higher the threat from outside. This is evidenced by the theft of wood, bamboo and other plants in the Temedak customary forest carried out by irresponsible people. For this reason, conservation attitude profile data is needed to identify categories of each indicator of students' conservation attitudes in protecting and overcoming surrounding biodiversity problems. This research uses quantitative descriptive method. Research participants included housewives, village shamans, local or community leaders. The instruments used are in the form of field notes of interview guidelines and conservation attitude questionnaires. The questionnaire was in the form of 38 statements tested to XI MIPA SMA students consisting of 40 respondents. Based on the results of the study, it was found that the Temedak customary forest has endemic plant species, namely pacat wood (Harpullia arborea) and carrion flowers namely Amorphophallus gigas. There are 57 types of plants that generally used by the people of Keluru Village such as foodstuffs, buildings, medicins, wicker, local technology and art, as well as for the benefit or complement of traditional ceremonies. The results of obtaining student conservation attitudes from 40 respondents showed differences in each indicator.